A ZIF-8 derived nanocatalyst doped hydrogel composite scaffold and its preparation method and application

By using ZIF-8 derived nanocatalysts doped with hydrogel composite scaffolds in bone tissue engineering scaffolds, the problem of insufficient catalytic decomposition ability and mechanical strength of ROS in the prior art is solved, and broad-spectrum catalytic elimination and bone regeneration of ROS are achieved. .

CN118949138BActive Publication Date: 2025-02-07NANKAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411440825.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing catalytic decomposition ROS bone tissue engineering scaffolds lack the catalytic decomposition ability and mechanical strength of broad-spectrum ROS, and the material itself does not have the ability to osteoinduce, making it difficult to achieve effective bone regeneration.

Method used

Using ZIF-8 derived nanocatalyst-doped hydrogel composite scaffolds, prepared by 3D printing technology, the broad-spectrum catalytic elimination of ROS is achieved in hydrogels using nitrogen-doped carbon nanocatalyst (ZIFC), and mixed double network water The gel structure enhances mechanical strength.

Benefits of technology

The efficient catalytic decomposition of ROS radicals and hydrogen peroxide was achieved, which improved the mechanical strength and osteoinduction of bone tissue engineering scaffolds, and promoted bone regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949138B_ABST
    Figure CN118949138B_ABST
Patent Text Reader

Abstract

The present invention relates to a ZIF-8 derived nanocatalyst doped hydrogel composite scaffold and its preparation method and application. The nitrogen-doped carbon material ZIFC nanocatalyst is obtained by high-temperature carbonization of ZIF-8 precursor, and the nanocatalyst is added to acrylamide / sodium carboxymethyl cellulose-based mixed double network hydrogel, and then calcium chloride is added to obtain the hydrogel composite scaffold by 3D printing. The composite scaffold successfully achieves broad-spectrum ROS catalytic decomposition, and has excellent mechanical strength and bone inductivity, which can effectively promote bone regeneration; and has high mechanical properties, which can be used to support bone regeneration at the bone defect site during bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic chemistry and relates to a method for preparing a hydrogel for catalytically decomposing ROS, in particular to a ZIF-8 derived nanocatalyst doped hydrogel composite scaffold and a preparation method and application thereof. Background Art

[0002] With the occurrence of diseases such as trauma, joint replacement, and tumor resection, large-area bone defects have become common diseases, and their treatment has always been a major clinical problem. Due to the serious complications, limited resources, and age restrictions of autologous bone transplantation and allogeneic bone transplantation, the development of advanced bone tissue engineering scaffolds is of great significance. Most bone tissue engineering scaffolds achieve bone regeneration by delivering cells or growth factors, but these bioactive materials have the limitations of short half-life, high production costs, and drug side effects. In addition, a large amount of reactive oxygen species (ROS) accumulates in the early stage of bone defects. Reactive oxygen species are a class of highly oxidizing byproducts produced by aerobic metabolism, including hydrogen peroxide, superoxide anions, and hydroxyl free radicals. Oxidative stress caused by excessive ROS can mediate severe inflammatory responses, induce apoptosis and necrosis of osteoblasts and osteocytes, inhibit osteogenic differentiation of mesenchymal cells, and hinder the formation of new bone. Therefore, the development of a bone tissue engineering scaffold that catalyzes the decomposition of ROS will effectively achieve bone regeneration.

[0003] Among the bone tissue engineering scaffolds that have been studied so far, there is a lack of broad-spectrum ROS catalytic decomposition ability, especially the catalytic decomposition and scavenging ability of ROS free radicals, and there is a lack of excellent mechanical strength. For example, Yanlin Wu et al. (Bioactive Materials, 2023, 20: 111–125) encapsulated polydopamine in gelatin, which could only eliminate hydrogen peroxide in ROS, and its mechanical strength was below 0.8 MPa; Jiaying Li et al. (Adv. Funct. Mater. 2022, 32, 2111208) encapsulated manganese dioxide nanoparticles in gelatin, which could only eliminate hydrogen peroxide in ROS, and its mechanical strength was below 0.025 MPa. In addition, the above materials for catalytic decomposition of ROS do not have bone induction ability, and bioactive factors are added to the composite scaffolds to promote bone regeneration.

[0004] Carbon materials have been found to have the potential for bone tissue repair. Their rich π-π bond structure is conducive to the adsorption of physiological ions and biomolecules, and contact with proteins and cells to promote the differentiation of progenitor cells into osteoblast lineages, showing excellent osteoinductivity. In addition, carbon materials are used as antioxidants due to their high stability in the harsh environment of the disease and their efficient ROS free radical scavenging ability. The carbon materials currently used mainly include carbon dots, carbon nanotubes, graphene and oxygen-modified derivatives, but they lack effective hydrogen peroxide catalytic decomposition ability, and their powder state cannot provide support at the bone defect site, thus limiting their application in bone tissue engineering. Hydrogel is one of the preferred materials for drug encapsulation and release. Its properties similar to those of the extracellular matrix make it have good biocompatibility, and its internal porous structure is conducive to the transportation of nutrients and metabolic waste. However, the single-network hydrogels that are currently used more often have low mechanical properties and cannot be used for load-bearing parts or to defend against external attacks; secondly, the bone defect site is usually irregular in shape, and personalized customized scaffolds through 3D printing are closer to clinical needs, but it is still difficult to make the hydrogel precursor have adjustable viscosity and rapid solidification.

[0005] In summary, the current hydrogel-catalyzed decomposition of ROS bone tissue engineering scaffolds has problems such as incomplete elimination of ROS species, low mechanical properties, excessive use of bioactive factors, and difficulty in 3D printing. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a ZIF-8 derived nano-catalyst doped hydrogel composite scaffold and a preparation method and application thereof.

[0007] The technical solution adopted by the present invention is: a method for preparing a ZIF-8 derived nanocatalyst doped hydrogel composite scaffold, which utilizes high-temperature carbonization of a ZIF-8 precursor to obtain a nitrogen-doped carbon nanocatalyst, adds the nitrogen-doped carbon nanocatalyst into an acrylamide-sodium carboxymethyl cellulose based mixed double network hydrogel, and obtains the hydrogel composite scaffold by 3D printing.

[0008] Preferably, the specific preparation method is as follows:

[0009] Step 1: The methanol solution of zinc salt and the methanol solution of 2-methylimidazole are mixed evenly and allowed to react at room temperature, and the obtained ZIF-8 powder is carbonized under a nitrogen atmosphere to obtain a ZIFC nanocatalyst;

[0010] Step 2: dissolving acrylamide in deionized water, adding ZIFC and ultrasonically dispersing, adding N,N-methylenebisacrylamide and initiator to the mixture, and stirring to obtain hydrogel bio-ink;

[0011] Step 3: The hydrogel bio-ink is formed into a pre-designed shape through 3D printing technology. Ultraviolet light is used during the printing process to further photo-cure the hydrogel structure to obtain a hydrogel composite scaffold.

[0012] Preferably, in step 1, the molar ratio of zinc salt, 2-methylimidazole and methanol is 1:1-8:800-1250; the zinc salt is one or more of zinc nitrate, zinc chloride and zinc acetate.

[0013] Preferably, the carbonization treatment temperature is 600°C-1100°C.

[0014] Preferably, the mass fraction of ZIFC is less than 2%.

[0015] Preferably, in step 2, sodium carboxymethyl cellulose and calcium chloride are also added to the hydrogel bio-ink, and the mass ratio of sodium carboxymethyl cellulose to calcium chloride is 1:1.0-1.5.

[0016] Preferably, the mass ratio of deionized water, acrylamide, ZIFC, sodium carboxymethyl cellulose, calcium chloride, N,N-methylenebisacrylamide and initiator is 100: 20–25: 0.1–2: 5–9: 5–13.5: 0.5–1: 0.9–2.

[0017] Preferably, the initiator is one or more of 2,2-azobis(2-methylpropylimidamide) dihydrochloride, ammonium persulfate, potassium persulfate, and tetramethylethylenediamine.

[0018] Preferably, in step three, after the hydrogel composite scaffold is printed, it is subjected to ultrasonic treatment at 40-60°C until it is completely cured.

[0019] The hydrogel bio-ink or hydrogel composite scaffold is prepared by the preparation method of ZIF-8 derived nano-catalyst doped hydrogel composite scaffold.

[0020] Application of hydrogel bio-ink or hydrogel composite scaffold in bone defect repair materials.

[0021] The advantages and positive effects of the present invention are: using ZIFC as a nanocatalyst can achieve a broad-spectrum catalytic elimination effect of ROS, ZIFC introduces nitrogen in situ to dope the carbon material, catalytically decomposes ROS, and can not only achieve efficient elimination of ROS free radicals, but also achieve efficient catalytic decomposition of hydrogen peroxide, so that the carbon material has a broad-spectrum catalytic elimination effect of ROS, which is closer to the elimination effect in vivo;

[0022] By selecting acrylamide as a covalent cross-linked hydrogel monomer and sodium carboxymethyl cellulose as a physical cross-linked hydrogel monomer, a new type of hybrid double network hydrogel structure can be formed. Compared with the covalent single network hydrogel or the physical single network hydrogel structure, its mechanical strength can be increased by at least 5 times; when used for bone defect repair, it can support bone regeneration at the bone defect site;

[0023] By introducing sodium carboxymethyl cellulose and calcium chloride and controlling their mass ratio within the range of 1:1.0–1.5, the hydrogel precursor can have a suitable viscosity, and its viscosity can be adjusted within a certain range to meet the extrudable properties and 3D printing requirements to achieve the repair of irregular bone defects; by introducing ZIFC catalytic nanoparticles, it can play a supporting role in the hydrogel network, thereby further enhancing the mechanical strength of the composite scaffold. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Digital photo of the 3D printed hydrogel composite scaffold Gel / ZIFC-1 obtained in Example 1;

[0025] Figure 2 Scanning electron microscope image of the 3D printed hydrogel composite scaffold Gel / ZIFC-1 obtained in Example 1;

[0026] Figure 3 Evaluation of 3D printed hydrogel composite scaffold Gel / ZIFC-1 and blank group for in vivo bone defect repair. DETAILED DESCRIPTION

[0027] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0028] The present invention relates to a ZIF-8 derived nanocatalyst doped hydrogel composite scaffold and its preparation method and application. ZIF-8 powder is synthesized by zinc salt and 2-methylimidazole, and ZIFC nanocatalyst is obtained after high temperature carbonization treatment. Acrylamide, N,N-methylenebisacrylamide and initiator are added to prepare hydrogel bio-ink, and the hydrogel composite scaffold can be prepared in a personalized manner through 3D printing technology. In order to improve the mechanical properties of the hydrogel composite scaffold, sodium carboxymethyl cellulose and calcium chloride can be added to the bio-ink, and then a hydrogel composite material with better antioxidant properties and better mechanical strength can be prepared through a suitable ratio.

[0029] ZIFC as a nanocatalyst can achieve a broad-spectrum catalytic elimination effect of ROS, and carbon materials or oxygen-doped carbon materials can achieve ROS free radical elimination. ZIFC can not only achieve efficient elimination of ROS free radicals, but also achieve efficient catalytic decomposition of hydrogen peroxide by in-situ introduction of nitrogen to dope carbon materials. ZIFC nanocatalysts have a graphene-like structure and abundant pyridinium nitrogen atoms, among which pyridinium nitrogen atoms have the ability to adsorb hydrogen peroxide, and then further combine with adjacent carbon atoms to break the OO bond of hydrogen peroxide. One of the -OH bonds captures hydrogen atoms to generate water, and then the formed NO bond continues to adsorb hydrogen peroxide to generate water and oxygen. At the same time, the NO bond is restored to the pyridinium nitrogen atom, realizing an efficient cyclic catalytic process. Selecting acrylamide as a covalent cross-linked hydrogel monomer and selecting sodium carboxymethyl cellulose as a physical cross-linked hydrogel monomer can form a new type of mixed double network hydrogel structure, and its mechanical strength can be increased by at least 5 times compared with covalent single network hydrogel or physical single network hydrogel structure. The introduction of ZIFC nanocatalysts can play a supporting role in the hydrogel network, thereby further enhancing the mechanical strength of the composite scaffold.

[0030] The specific preparation method of the hydrogel composite scaffold is as follows:

[0031] Step 1: Synthesis of nitrogen-doped carbon nanocatalyst (ZIFC) derived from ZIF-8; a methanol solution containing zinc salt and a methanol solution containing 2-methylimidazole are mixed evenly and then allowed to stand at room temperature for at least 12 hours, a solid sample is collected and thoroughly dried to obtain a white powder, wherein the molar ratio of zinc salt, 2-methylimidazole and methanol is 1: 1–8: 800–1250; the ZIF-8 powder is then placed in a nitrogen-protected tubular furnace for high-temperature carbonization treatment for at least 2 hours, the carbonization temperature being 600°C–1100°C, to obtain a ZIFC nanocatalyst; wherein the zinc salt is one or more of zinc nitrate, zinc chloride and zinc acetate;

[0032] Step 2: Synthesis of hydrogel bio-ink; dissolving covalently cross-linked hydrogel monomer acrylamide in deionized water, then adding ZIFC nanocatalyst and ultrasonically dispersing, then adding sodium carboxymethyl cellulose and continuing to stir for at least 0.5 hours; then adding calcium chloride and stirring for at least 0.5 hours, the mass ratio of sodium carboxymethyl cellulose to calcium chloride is 1: 1.0-1.5; then adding N,N-methylenebisacrylamide and initiator to the above mixture in sequence, stirring for at least 0.5 hours, and obtaining hydrogel bio-ink; wherein the mass ratio of deionized water, covalently cross-linked hydrogel monomer, ZIFC, sodium carboxymethyl cellulose, calcium chloride, N,N-methylenebisacrylamide and initiator is 100: 20-25: 0.1-2: 5-9: 5-13.5: 0.5-1: 0.9-2;

[0033] The covalently cross-linked hydrogel monomer is acrylamide; the initiator is one or more of 2,2-azobis(2-methylpropylimidamide) dihydrochloride, ammonium persulfate, potassium persulfate, and tetramethylethylenediamine; wherein acrylamide is a covalently cross-linked single-network hydrogel monomer, which forms a covalently cross-linked single-network hydrogel after the cross-linker N,N-methylenebisacrylamide and the initiator react together; carboxymethyl cellulose and calcium chloride constitute a physically cross-linked single-network hydrogel; the two single-network hydrogels are integrated to obtain a mixed double-network hydrogel; step three: the hydrogel bio-ink is formed into a pre-designed shape through 3D printing technology, ultraviolet light is used for irradiation during the printing process, so that the hydrogel structure is further photocured, and after the composite scaffold is printed, the sample is ultrasonically treated at 40-60°C for 1-2 hours to completely cure to obtain a hydrogel composite scaffold, and the sample is taken out and sealed for storage.

[0034] As a nanocatalyst, ZIFC can achieve a broad-spectrum ROS elimination effect. By in-situ introduction of nitrogen to dope carbon materials, ZIFC can not only achieve efficient elimination of ROS free radicals, but also achieve efficient catalytic decomposition of hydrogen peroxide, so that the carbon material has a broad-spectrum ROS catalytic elimination effect, which is closer to the in vivo elimination effect. In addition, by introducing sodium carboxymethyl cellulose and calcium chloride and controlling their mass ratio within the range of 1: 1.0-1.5, the hydrogel precursor can have a suitable viscosity, and its viscosity can be adjusted within a certain range to meet the extrudable characteristics and the 3D printing requirements of special shapes.

[0035] Based on the above characteristics, the hydrogel composite scaffold prepared by this method can be used for bone tissue engineering scaffolds, and can be used as a hydrogel composite scaffold that catalyzes and decomposes ROS to resist inflammation and promote bone regeneration, and can be used to replace bone powder to repair bone defects and promote bone regeneration. When used, the hydrogel composite scaffold can achieve broad-spectrum ROS catalytic elimination, improve the mechanical strength of the scaffold, and achieve bone inductivity with inorganic particles, thereby overcoming the problems of unsatisfactory catalytic decomposition of ROS in bone tissue engineering scaffolds, poor mechanical properties, side effects of bioactive factors, and inability to repair irregular bone defects. The 3D-printed hydrogel composite scaffold that catalyzes and decomposes ROS to resist inflammation and promote bone regeneration, while providing excellent mechanical strength, achieves broad-spectrum ROS catalytic elimination and bone inductivity to achieve anti-inflammation to promote bone regeneration.

[0036] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.

[0037] Example 1

[0038] (1) A methanol solution containing zinc nitrate and a methanol solution containing 2-methylimidazole were mixed evenly and allowed to stand at room temperature for 24 hours. The sample was then centrifuged and washed with methanol and thoroughly dried to obtain a white ZIF-8 powder, wherein the molar ratio of zinc nitrate, 2-methylimidazole and methanol was 1:4:800; the ZIF-8 powder was then placed in a nitrogen-protected tubular furnace and subjected to high-temperature carbonization treatment at 800°C for 2 hours to obtain a ZIFC material;

[0039] (2) Under stirring at room temperature, acrylamide was dissolved in deionized water, and then ZIFC was added and ultrasonically dispersed, and then sodium carboxymethyl cellulose was added and stirred for 0.5 hour; then calcium chloride was added and stirred for 0.5 hour, and then N,N-methylenebisacrylamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride were added to the above mixture in sequence and stirred for 0.5 hour to obtain hydrogel bio-ink; wherein the mass ratio of deionized water, acrylamide, ZIFC, sodium carboxymethyl cellulose, calcium chloride, N,N-methylenebisacrylamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride was 100:20:1.5:5:5:0.5:0.9.

[0040] (3) The hydrogel bio-ink was loaded into the sample tube of the 3D printer and printed according to the designed 3D model. During the printing process, the printed hydrogel structure was irradiated with ultraviolet light to further photocuring the hydrogel structure. After the printing was completed, the sample was ultrasonically treated at 40 °C for 1 hour to completely cure. The sample was then taken out and sealed for storage to obtain the hydrogel composite scaffold Gel / ZIFC-1. The digital photo of the hydrogel composite scaffold Gel / ZIFC-1 is shown in the figure. Figure 1 As shown, the prepared hydrogel bio-ink can be successfully printed to obtain a fixed shape; a composite material with a pore size of about 500 microns can be printed according to demand, which is suitable for cell shuttling and infiltration in the body, and is conducive to the repair effect of subsequent animal in vivo experiments. Figure 2 As shown, it can be seen that the interior of the hybrid double-network hydrogel presents a loose, porous and interconnected pore structure, and the pore size is concentrated in the range of 1-3 microns, which is conducive to the efficient transmission and exchange of physiological ions in the body.

[0041] Example 2

[0042] The preparation steps of Example 2 are the same as those of Example 1, except that zinc nitrate in step (1) is replaced by zinc chloride. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-2.

[0043] Example 3

[0044] The preparation steps of Example 3 are the same as those of Example 1, except that the carbonization temperature in step (1) is changed to 1100° C. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-3.

[0045] Example 4

[0046] The preparation steps of Example 4 are the same as those of Example 1, except that the mass ratio of sodium carboxymethyl cellulose to calcium chloride in step (2) is changed to 1:1.5. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-4.

[0047] Example 5

[0048] The preparation steps of Example 5 are the same as those of Example 1, except that half of the 2,2-azobis(2-methylpropylimidazole) dihydrochloride initiator in step (2) is replaced by ammonium persulfate, that is, a mixture of equal masses of 2,2-azobis(2-methylpropylimidazole) dihydrochloride and ammonium persulfate is used as the initiator. The resulting hydrogel composite scaffold is numbered Gel / ZIFC-5.

[0049] Example 6

[0050] The preparation steps of Example 6 are the same as those of Example 1, except that the mass ratio of deionized water to ZIFC in step (2) is changed to 100:0.5. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-6.

[0051] Example 7

[0052] The preparation steps of Example 7 are the same as those of Example 1, except that the ultrasonic curing time in step (3) is changed to 2 hours. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-7.

[0053] Comparative Example 1

[0054] The purpose is to compare with Example 1 to illustrate the effect of the carbonization temperature of the ZIF-8 precursor on the oxidation resistance of ZIFC.

[0055] The preparation steps of Comparative Example 1 are the same as those of Example 1, except that the carbonization temperature in step (1) is changed to 500° C. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-8.

[0056] Comparative Example 2

[0057] The purpose is to compare with Example 1 to illustrate the effect of a larger mass ratio of sodium carboxymethyl cellulose to calcium chloride on the mechanical strength of the composite scaffold.

[0058] The preparation steps of Comparative Example 2 were the same as those of Example 1, except that the mass ratio of sodium carboxymethyl cellulose to calcium chloride in step (2) was changed to 1:0.8. The obtained hydrogel composite scaffold was numbered Gel / ZIFC-9.

[0059] Comparative Example 3

[0060] The purpose is to compare with Example 1 to illustrate the effect of a relatively small mass ratio of sodium carboxymethyl cellulose to calcium chloride on the mechanical strength of the composite scaffold.

[0061] The preparation steps of Comparative Example 3 were the same as those of Example 1, except that the mass ratio of sodium carboxymethyl cellulose to calcium chloride in step (2) was changed to 1:1.8. The obtained hydrogel composite scaffold was numbered Gel / ZIFC-10.

[0062] Comparative Example 4

[0063] The purpose is to compare with Example 1 to illustrate the effect of the double network hydrogel formed by introducing sodium carboxymethyl cellulose and calcium chloride on the mechanical strength.

[0064] The preparation steps of Comparative Example 4 are the same as those of Example 1, except that the step of adding sodium carboxymethyl cellulose and calcium chloride in step (2) is removed. The obtained hydrogel composite scaffold is numbered Gel / ZIFC-11.

[0065] Comparative Example 5

[0066] The purpose is to compare with Example 1 to illustrate the effect of introducing too much ZIFC on the mechanical strength and curing speed of the gel.

[0067] The preparation steps of Comparative Example 5 were the same as those of Example 1, except that the mass ratio of deionized water and ZIFC used in step (2) was changed to 100:2.5. The obtained hydrogel composite scaffold was numbered Gel / ZIFC-12.

[0068] Example 8: Detection of hydrogel composite scaffold

[0069] 8.1 Characterization of Mechanical Properties of Hydrogels Catalyzed by ROS Decomposition

[0070] The hydrogel bio-ink obtained in step (2) of Examples 1, 4, 5, 6, 7 and Comparative Examples 2, 3, 4, 5 was squeezed into a customized cylindrical polytetrafluoroethylene mold and irradiated with a UV lamp to cure it to obtain a hydrogel cylinder. The mechanical properties of the hydrogel cylinder were measured by a universal testing machine (Instron 5567, Instron, USA). The specific implementation method was as follows: the hydrogel cylinder was installed between two parallel pressing plates and the pressure was adjusted at 5 mm / min. -1The hydrogel cylinder was compressed at a constant strain rate until it was completely damaged, and the mechanical strength value was obtained.

[0071] The mechanical strength results of Gel / ZIFC-1, Gel / ZIFC-4 to Gel / ZIFC-7, Gel / ZIFC-9 to Gel / ZIFC-12 are shown in Table 1. Compared with the comparative example, the hydrogel composite scaffolds prepared in Examples 1, 4, 5, 6, and 7 have stronger mechanical strength.

[0072] Table 1

[0073]

[0074] 8.2 Catalytic Decomposition of ROS Broad-spectrum ROS Catalytic Elimination Ability of Hydrogel Scaffolds

[0075] The catalytic effect of Examples 1, 2, 3, 6 and Comparative Example 1 on hydrogen peroxide was evaluated by a hydrogen peroxide content detection kit (Solabo: BC3590). The catalytic elimination ability of Examples 1, 2, 3, 6 and Comparative Example 1 on superoxide anions was evaluated by a superoxide dismutase activity detection kit. 3+ The hydroxyl radicals produced by the reaction of hydrogen peroxide and salicylic acid were evaluated by the catalytic elimination ability of Examples 1, 2, 3, 6 and Comparative Example 1 on hydroxyl radicals to obtain the corresponding catalytic elimination efficiencies.

[0076] The ROS elimination results of Gel / ZIFC-1 to Gel / ZIFC-3, Gel / ZIFC-6, and Gel / ZIFC-8 are shown in Table 2. From the data in the table, it can be seen that compared with the comparative example, the hydrogel composite scaffold prepared in the example has an outstanding ability in removing hydrogen peroxide and superoxide anions, and can generate more hydroxyl radicals.

[0077] Table 2

[0078]

[0079] 8.3 Evaluation of the bone defect repair effect of hydrogel scaffolds catalyzed by ROS decomposition

[0080] The bone defect repair effect of the catalytic decomposition ROS hydrogel composite scaffold in Example 1 was evaluated based on the SD rat skull defect model. First, two circular bone defects with a diameter of 5 mm were made on both sides of the rat skull suture, and then the wound was left untreated (blank group) and the catalytic decomposition ROS hydrogel scaffold (composite scaffold group) was placed for experiments. Skull samples of the blank group and the catalytic decomposition ROS scaffold group were collected at 6 weeks and 12 weeks for micro-CT scanning and reconstruction. The result is shown in Figure 3. It can be seen that the hydrogel composite scaffold prepared by the embodiment is filled into the rat bone defect position, which can significantly improve the bone healing rate and promote bone regeneration.

[0081] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of application of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing an antioxidant ZIF-8 derived nitrogen-doped hydrogel composite scaffold, characterized in that: The nitrogen-doped carbon material was obtained by high-temperature carbonization of ZIF-8 precursor, which was added into acrylamide-sodium carboxymethyl cellulose-based mixed double network hydrogel to obtain a hydrogel composite scaffold by 3D printing. The specific preparation method is as follows: Step 1: The methanol solution of zinc salt and the methanol solution of 2-methylimidazole are mixed evenly and then allowed to react at room temperature. The obtained ZIF-8 powder is carbonized under a nitrogen atmosphere to obtain antioxidant particles ZIFC; the molar ratio of zinc salt, 2-methylimidazole and methanol is 1: 1–8: 800–1250; Step 2: dissolving acrylamide in deionized water, adding ZIFC and ultrasonically dispersing, adding sodium carboxymethyl cellulose and calcium chloride, adding N,N-methylenebisacrylamide and initiator to the above mixture, and stirring to obtain hydrogel bio-ink; the mass ratio of deionized water, acrylamide, ZIFC, sodium carboxymethyl cellulose, calcium chloride, N,N-methylenebisacrylamide and initiator is 100: 20–25: 0.1–2: 5–9: 5–13.5: 0.5–1: 0.9–2; Step 3: The hydrogel bio-ink is formed into a pre-designed shape through 3D printing technology. Ultraviolet light is used during the printing process to further photo-cure the hydrogel structure to obtain a hydrogel composite scaffold.

2. The method for preparing the antioxidant ZIF-8 derived nitrogen-doped hydrogel composite scaffold according to claim 1, characterized in that: The zinc salt is one or more of zinc nitrate, zinc chloride and zinc acetate.

3. The method for preparing the antioxidant ZIF-8 derived nitrogen-doped hydrogel composite scaffold according to claim 1, characterized in that: The carbonization treatment temperature is 600℃–1100℃.

4. The method for preparing the antioxidant ZIF-8 derived nitrogen-doped hydrogel composite scaffold according to claim 1, characterized in that: The initiator is one or more of 2,2-azobis(2-methylpropylimidamide) dihydrochloride, ammonium persulfate, potassium persulfate, and tetramethylethylenediamine.

5. The method for preparing the antioxidant ZIF-8 derived nitrogen-doped hydrogel composite scaffold according to claim 1, characterized in that: In step three, after the hydrogel composite scaffold is printed, it is ultrasonically treated at 40–60 °C until it is completely cured.

6. The hydrogel bio-ink or hydrogel composite scaffold prepared by the method for preparing the antioxidant ZIF-8 derived nitrogen-doped hydrogel composite scaffold according to any one of claims 1 to 5.

7. Use of the hydrogel bio-ink or hydrogel composite scaffold described in claim 6 in bone defect repair materials.

Citation Information

Patent Citations

  • MOF / cellulose hydrogel as well as preparation method and application thereof

    CN116751374A